Современи аспекти на системот на финансирање на здравствената заштита во Република Македонија - Малоски, Ракип (Економски факултет, УКИМ, Скопје, 2014)
Inadequate financing in health care as manifested by low and weak connection between the system of health services and funds for financing in health care, is an indicator of a lack of regulatory and control mechanisms. Hence, there is a need for providing adequate financing in the health care for the entire population in the country, while providing health services for the population groups who are poor and unable to pay contributions for compulsory health insurance, and yet they need the essential health care. In providing health care in Macedonia, the primary problem is funding, but here are immediately recognized limitations or the limited capacity of the institutions where there is a need for a scientific approach to the study of the health care or the system of financing in health care in the country. For this purpose we should target the weaknesses of the institutions, and then a very important segment of the statewide upgrade of the financial management in the health sector, is the control of corruption, to show better results in categories such as health care management, as a part of the public sector and social inclusion policy. Other targets in the improvement of health care in the evaluation of its effectiveness are those relating to inequality and disproportion of the funds from the state budget for funding health services. This research will try to study, analyze and process the information and data that reflect the financing in health care. The results of this analysis later will be used to improve and make more efficient implementation of funding in health sector.
Contemporary aspects of the health care financing system in the Republic of Macedonia
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Пеце Недановски.
Keywords: health care financing, health services, health personnel, health care organizations, health insurance, health costs, health benefits, Republic of Macedonia